Analytic Evaluation of Input Impedance of an Equilateral Triangular Dielectric Resonator Antenna. Issue 3 (4th May 2022) - Maity, Sudipta; Gupta, Bhaskar
Abstract : In this paper, analytical expressions are given to evaluate the input impedance of a probe-fed (inserted) Equilateral Triangular Dielectric Resonator Antenna (ETDRA) for different T M m n p z modes for the first time. Theoretical results are verified with measured data as found in the literature and data obtained using a 3D EM simulator HFSS for fundamental T M 101 z mode for arbitrary dimensions and relative permittivity ( ε r = 12, 50   and   100 ) . Good agreement is found between our theory and measured (and simulated) data.